Um estudo sobre a rotatividade de pessoal entre profissionais de empresas brasileiras de desenvolvimento de software - Frufrek, Guilherme Luiz (2015)
Employee turnover is one of the major challenges for many software development companies. This work presents a study to identify the main causes and effects of employee turnover among professionals of Brazilian software development companies. Strategies applied to minimize employee turnover and its effects were also investigated. A survey methodology was used to collect data from software development professionals. Data collection was performed using the technique of questionnaire with closed questions using five-point Likert scale and multiple choice questions. Cronbach’s alpha coefficient was applied to check the reliability of the answers. The analysis of data from 67 respondents was conducted through descriptive statistics and inferential statistics. The results indicate that inappropriate management style, personal expectation not achieved within the company, lack of professional recognition, and lack of organizational involvement influences the decision of professionals to leave the company. These factors can contribute decisively in rates of employee turnover. The results also indicate other aspects, related to the employee, which are important for turnover intention. The company must be concerned with factors that can motivate the employee to stay with the company, such as communication, career plan, work environment, promotion for performance, and periodic training.